COMPLIANCE OF EXERCISE IN PATIENTS WITH ANKYLOSING SPONDYLITIS IN LOWER MIDDLE-INCOME COUNTRY - ISHAQUE, M; ROSHAN, I; HABIB, G; KHILJI, Z; MOHIBULLAH, M; REHMAN, FU; MANSOOR, J; USMAN, M (Biological and Clinical Sciences Research Journal, 2024)
Exercise adherence is crucial for the management of patients with ankylosing spondylitis (AS), particularly in reducing symptoms and improving quality of life. However, barriers to exercise adherence in this patient population remain poorly studied, especially in resource-poor settings. This study focused on assessing exercise adherence among AS patients in Quetta, Pakistan, identifying both challenges and facilitators of adherence. Objective: The objective of this study was to assess exercise adherence among AS patients in Quetta, Pakistan, and explore key factors influencing their adherence to prescribed exercise programs, including barriers such as physical limitations, financial constraints, and social and support systems. Methods: This descriptive cross-sectional study was conducted in several rheumatology outpatient clinics in Quetta from January to July 2024. A purposive sample of 20 AS patients was recruited and a self-administered questionnaire was used to collect clinical and demographic data. Thematic analysis was performed to identify key themes related to exercise adherence, including facilitators and barriers. Results: Of the 20 participants, 60% were male and 40% were female, with a mean age of 45 years. Thematic analysis revealed four key themes: physical barriers (including chronic pain and fatigue), financial challenges (such as not being able to afford a gym membership or transportation), social factors (including stigma and lack of support), and motivational influences. Despite these barriers, social support and personalized exercise prescriptions emerged as key facilitators of adherence. Participants who received personalized exercise programs and education on the benefits of physical activity had higher adherence rates. Conclusion: Exercise adherence among AS patients in Quetta is influenced by a complex interaction of physical, social, and financial factors. Eliminating these barriers through patient-centred strategies, including personalized exercise programs and increased social support, can significantly improve adherence. These findings highlight the need for personalized approaches to promote physical activity among patients with AS, especially in resource-poor settings such as Quetta.